Large Meteorite Impacts III 2005
DOI: 10.1130/0-8137-2384-1.43
|View full text |Cite
|
Sign up to set email alerts
|

Using vertical dikes as a new approach to constraining the size of buried craters: An example from Lake Wanapitei, Canada

Abstract: Lake Wanapitei, located within the Southern Province of Ontario, Canada, provides the setting for a unique study of an impact crater situated within a shield environment. Evidence for the 7.5-km-diameter Wanapitei impact includes a circular Bouguer gravity low centered over the central area of the lake and features of shock metamorphism in samples of glacial drift found on the southern shores. Geophysical studies of craters in hard-rock environments are often limited by the lack of markers used for exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This kind of target lithology makes its identification more difficult, because stratified targets provide better evidence of impact. This 7-km structure, however, is also the host of a dike swarm of 1200 Ma, a feature that helps the comprehension of the rocks below the surface based on magnetic studies (L'Heureux et al 2005). Ugalde et al (2006) suggest that the N-S trend observed in the gravity anomaly map is related to a regional fault zone of 2200-1900 Ma that has gone through reactivation over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This kind of target lithology makes its identification more difficult, because stratified targets provide better evidence of impact. This 7-km structure, however, is also the host of a dike swarm of 1200 Ma, a feature that helps the comprehension of the rocks below the surface based on magnetic studies (L'Heureux et al 2005). Ugalde et al (2006) suggest that the N-S trend observed in the gravity anomaly map is related to a regional fault zone of 2200-1900 Ma that has gone through reactivation over time.…”
Section: Discussionmentioning
confidence: 95%
“…This 7‐km structure, however, is also the host of a dike swarm of 1200 Ma, a feature that helps the comprehension of the rocks below the surface based on magnetic studies (L'Heureux et al. ). Ugalde et al.…”
Section: Discussionmentioning
confidence: 99%
“…Careful observation suggests the presence of a characteristic pattern of dyke swarms, that is, those dykes remain parallel to subparallel to each other. The dyke swarm at Lake Wanapitei is assumed to be associated with Precambrian Matachewan and Sudbury dyke swarms (L'Heureux et al ., 2005), and such a swarm is interpreted to be due to the mantle plume effect (Ernst et al ., 1995).…”
Section: Numerical Experimentsmentioning
confidence: 99%